A COMPARISON BETWEEN GRAMMAR-TRANSLATION METHOD AND DIRECT METHOD IN IMPROBING PUPIL’S VOCAB ULARY ACHIEVEMENT - Caroline V. Katemba (Journal of Language Pedagogy, 2011)
ABSTRACT Nowadays, many language teachers use different kinds of teaching method. Applying a certain method is one of the important factors in language teaching, especially in teaching vocabulary. Vocabulary is one of the most important parts in learning a language. Therefore, teacher has to be more concern on the method for the effectiveness of the process itself. From the above reason, this study entitled " Comparison between Grammar-Translation Method and Direct Method in Improving Students' Vocabulary Achievement" was employed to examine their difference in teaching vocabulary to the pupils. The participants were grade 6 pupils of Karyawangi Elementary School Parongpong, Bandung. This study was divided into three sessions: the pre-test, the implementation of Grammar-Translation Method and Direct Method, and the postÂtest. In the pre-test and post-test, the multiple-choice test was administered to them. In the treatment session, the researcher taught Grammar-Translation Method (GTM) to one group and the other group with the Direct Method (DM). The data obtained as follows: n1 (GTM group population) = 31, n2 (DM group population) = 27, a = 0.05. The mean of the pre-test of GTM group was 29.61 and the mean of Direct Method was 36.37. After the treatments, the mean of the post-test of GTM group was 46.45 while the mean of the post-test of DM group was 46.22. The range mean of GTM group was 16.84 while the DM group was 9.85. It means that there is a significant difference on the pupils' vocabulary improvement. It can also be concluded that Grammar-Translation Method is better than Direct Method in improving pupils' vocabulary achievement. Â  Keywords: Grammar-translation, Direct method